2015
DOI: 10.1016/j.tetlet.2015.02.059
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and investigation of novel spiro-isoxazolines as anti-cancer agents

Abstract: A series of structurally diverse 4-bromo spiro-isoxazolines possessing a variety of aromatic and aliphatic substituents at the 3 position, were synthesized through a 1,3-dipolar cycloaddition followed by intramolecular cyclization of a pendant hydroxyl or carboxylic acid group. The biochemical antiproliferative activity was evaluated in vitro by using two breast cancer cell lines (MCF-7 and MDA-MB-231) and two prostate cancer cell lines (PC-3 and DU-145) using the MTT viability assay, and the IC50 values were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…The antiproliferative effect was more pronounced with spiro-isoxazole (3). Structurally, the presence of the isoxazole heterocyclic unit is likely tightly related to these clear antiproliferative effects, as already reported for other spiro-models containing the isoxazole motif (7). It was also observed that the presence of oxazepine substituent demonstrated good activity against breast cancer cells (26), thus explaining the antiproliferative effect observed with compound 6.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The antiproliferative effect was more pronounced with spiro-isoxazole (3). Structurally, the presence of the isoxazole heterocyclic unit is likely tightly related to these clear antiproliferative effects, as already reported for other spiro-models containing the isoxazole motif (7). It was also observed that the presence of oxazepine substituent demonstrated good activity against breast cancer cells (26), thus explaining the antiproliferative effect observed with compound 6.…”
Section: Discussionsupporting
confidence: 65%
“…Various spiro-isoxazolidine ( Figure 1C) derivatives were prepared and tested for their anticancer activity against human cancer cell lines. Moreover, several 4-bromo spiro-isoxazoline structures have also shown antiproliferative effects against breast and prostate cancer cell lines (7).…”
mentioning
confidence: 99%
“…Antiproliferative activity of the compounds was evaluated in vitro by using two breast cancer cell lines (MCF-7 and MDA-MB-231) and two prostate cancer cell lines (PC-3 and DU-145) using the MTT viability assay, and IC 50 values were obtained [12].…”
Section: Library Applicationsmentioning
confidence: 99%
“…Due to the wide range of biological and medicinal activities the synthesis of spiro compounds has become a significant target over the past decade. 1 H ‐indole‐2,3‐diones (isatins) are important core structures, able to form a large number of both naturally occurring and synthetic spiroheterocycles and know to exhibit several biological activities like antiinflammatory, and laxative agents, antibacterial, antimicrobial, antimalaria, antitumor, antitubercular, and anti‐HIV …”
Section: Introductionmentioning
confidence: 99%